Modeling of Waterlogging Condition on a River Basin - Ray, R; Patra, S K; Mukhopadhyay, K (Journal of Agricultural Engineering, 2004)
Using the 3-years rainfall data, a simple mathematical model has been developed to predict the time of occurrence of waterlogging condition in representative lowland of Dankuni basin. It was found that rainfall alone could account for over 95% variations of waterlogging between 30 and 50% rainfall probability levels. This information seems to be reasonably good in estimating the design drainage discharge required to adopt a suitable cropping pattern. The model, however, needs to be refined and upgraded after incorporating long duration rainfall and water stagnation data from a few strategic points of the entire basin for validation with a view to formulating a surface drainage design.